1998
DOI: 10.1128/jvi.72.12.9818-9826.1998
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cell Polarity on Retrovirus-Mediated Gene Transfer to Differentiated Human Airway Epithelia

Abstract: Gene transfer with recombinant murine leukemia viruses (MuLV) provides the potential to permanently correct inherited lung diseases, such as cystic fibrosis (CF). Several problems prevent the application of MuLV-based recombinant retroviruses to lung gene therapy: (i) the lack of cell proliferation in mature pulmonary epithelia, (ii) inefficient gene transfer with a vector applied to the apical surface, and (iii) low titers of many retroviral preparations. We found that keratinocyte growth factor (KGF) stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 51 publications
6
55
0
Order By: Relevance
“…Infection of epithelial cells by most viruses is polarized in terms of entry and release of virus particles (reviewed in (41)). We noted previously that entry of Moloney murine retrovirus vectors with amphotropic or xenotropic envelopes into human airway epithelia was restricted to the basolateral surface (21). In contrast, influenza virus infection resulted from binding to the apical plasma membrane ((32) and this study), similar to coronavirus (42,43) and measles virus (44).…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Infection of epithelial cells by most viruses is polarized in terms of entry and release of virus particles (reviewed in (41)). We noted previously that entry of Moloney murine retrovirus vectors with amphotropic or xenotropic envelopes into human airway epithelia was restricted to the basolateral surface (21). In contrast, influenza virus infection resulted from binding to the apical plasma membrane ((32) and this study), similar to coronavirus (42,43) and measles virus (44).…”
Section: Discussionsupporting
confidence: 56%
“…In contrast, influenza virus infection resulted from binding to the apical plasma membrane ((32) and this study), similar to coronavirus (42,43) and measles virus (44). Researchers investigating viral vectors for application to the treatment of cystic fibrosis have shown that one of the major limitations to infection of airway epithelia from the apical side is receptor inaccessibility (21)(22)(23)(24). Recently, methods have been developed to transiently disrupt the tight junctions to allow envelope viruses access to all cell layers of the epithelia (45).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations